EFFECT OF CO-CURRICULAR AND EXTRA-CURRICULAR ACTIVITITES ON STUDENTS’ PERFORMANCE: A CASE STUDY OF ISLAMIA COLLEGE PESHAWAR - Sehran Hassan; Muhammad Ismail; Fazal Shakoor; Anwar Ali; Nadeem Khan; Nabeel Khan; Dr. Soofia Iftikhar (International Journal of Contemporary Issues in Social Sciences, 2024)
Education plays a vital role in the development of a nation. The favorable outcomes of educational institutes are best judged by the performance of their students. There are different factors which influence the academic performance of the students, such as availability of qualified teachers, study hours and internet facilities etc. The current study has been conducted to investigate the effect of extra-curricular activities on students’ performance. The data was collected from 254 students of Islamia College, Peshawar. Data was analyzed by Statistical Software for Social Sciences (SPSS) version 25. Both descriptive and inferential statistics were used to analyze the collected data. For descriptive analysis the percentages of various categories of the variables have been calculated and interpreted. For inferential analysis of the collected data, the Chi-Square test for independence was used. The results indicate that gender and area type are significant while the rest of factors like use of internet, home-based activities part-time job and attending seminar etc. are found to have insignificant effects on students’ performance.